Clinical Significance of Intra-Abdominal Hypertension - Kyu-Hyouck Kyoung (Journal of Acute Care Surgery, 2016)
Intra-abdominal hypertension (IAH) is defined as steady state pressure in the abdominal cavity. Intra-abdominal pressure (IAP) acts as resistance against blood flow. IAH decreases abdominal perfusion pressure, aggravates hemodynamics and organ dysfunction and raises serious risks of morbidity and mortality. IAP should be a goal of resuscitation, and aggressive treatment should be performed to relieve IAH, including therapeutic open abdomen.